CHARACTERISTICS OF COPING STRATEGIES RELATED TO STRESS FOR PHYSICAL EDUCATION AND SPORTS TEACHERS - N. Kostova; D. Kaykov (Trakia Journal of Sciences, 2024)
Each person’s activities and efforts are related to dealing with different situations with varying stress levels. For every person this is known to lead to the formation of an individual structure of different coping strategies related to the perceived level of stress. The adequacy of this structure is entirely dependent on the efficiency of each person’s actions and is a basis for its own refinement. Given that the structure of coping strategies is inadequate, this can lead to hindered possibilities for growth and hence, a lower quality of life. The aim of this studyis to establish the key features of coping strategies for Physical Education and Sports (PES) teachers. To achieve this goal, a review of literature was carried out, with the addition of live observations and discourse with the participants of the study. The teachers’ coping strategies were evaluated with the COPE-1 questionnaire. The obtained data was analyzed via descriptive statistics, hypothesis testing, correlation analysis, hierarchical clustering and t-SNE dimensionality reduction. Resultsfrom the analyses are presented in their respective graphs. During the interpretation of the results, it was established that the studied male and female PES teachers have well-structured coping strategies. The main established ones are Active coping, Planning, and Positive reinterpretation and growth. It was also established that the teachers from the studied sample rarely rely on strategies such as Turning to religion, Acceptance, Behavioral disengagement and Alcohol-drug disengagement.